An endless identity dilemma: the liminal westernised Muslim malays in the enemy in the blanket by Anthony Burgess - Bahar, Ida Baizura; Kamarudin, Kamariah; Maming, Pabiyah; Abd Razak, Farahanna (Australian International Academic Centre, 2019)
The second installment of The Malayan Trilogy (1964), The Enemy in the Blanket (1958), an English literary text by Anthony Burgess (1917-1993), is written with the colliding of cultures and clashes of religions as the central themes. Set in pre-independence Malaya, Burgess is part of a group of Western writers who had actually lived in their fictional settings where the literary continuation of this group of writers has been ignored for a long time and has not appeared in anthologies in the academic context. As scholarship on the Muslim Malay characters in Burgess’ novel is still overlooked in terms of scholarly value as well as its Islamic and Malay ethnicity discourses, we argue that Burgess has addressed a conundrum still faced by current Muslim Malay society: the pre-independence Muslim Malay characters in The Enemy in the Blanket are conflicted; trapped in a state of betwixt and between being a Muslim, and of a Westernised lifestyle which, more often than not, oppose each other. Thus, we examine Burgess’ portrayals of the Muslim Malay characters that adopt a Westernised lifestyle and appear to be in a quandary with regards to their Islamic beliefs and practices. As methodology, we utilised Victor Turner’s concept of liminality (1967) to analyse scenes in the novels which depict such binary opposition. Findings demonstrate that the Muslim Malay characters have to negotiate their identity issues in order to either feel more socially acceptable through the preference of a Westernised lifestyle or struggle to become ethically and morally truthful to their religious faith.